On the genera Issidius Puton and Morsina Melichar (Hemiptera: Auchenorrhyncha: Fulgoroidea: Nogodinidae: Epacriini) - Gnezdilov, Vladimir M.; Mozaffarian, Fariba (Zootaxa, 2020)
Nogodinid genera Issidius Puton, 1898 and Morsina Melichar, 1902 are revised. Iranissus Dlabola, 1980 is placed in synonymy under Issidius Puton and Hadjia Dlabola, 1981, Philbyella China, 1938 and Rileyopsis Bergevin, 1917—under Morsina Melichar. Philbyella adeiba Badawy, El Hamouly et Sawaby, 2011 is placed in synonymy under Ph. elba Linnavuori, 1973. The lectotypes are designated for Issus rotundiceps Lethierry, 1887 and Morsina persica Melichar, 1902. The photos of type specimens of Morsina persica Melichar, 1902, Hadjia quadrifasciata Dlabola, 1981, and H. nerii Dlabola, 1981 are given.